Comparative safety and efficacy of midline catheters versus long peripheral catheters in patients undergoing bariatric surgery: a randomised controlled trial - Linfang Zhao; Xiaohui Yang; Chang Liu; Weihua Yu; Xiuzhu Cao; Xiangyun Li; Jie Wang; Yiyu Zhuang (Scientific Reports)
Abstract Bariatric surgery is an effective treatment for moderate-to-severe obesity, however, reliable vascular access during the perioperative period remains a challenge in this population. This study compared the safety and efficacy of midline catheters (MCs) and long peripheral catheters (LPCs) in patients who underwent bariatric surgery. This single-blind, randomised controlled trial was conducted at a tertiary acute hospital between September 2023 and January 2024. A totol of 224 patients were assigned to receive either MC or LPC. The primary outcome was catheter failure; secondary outcomes included insertion attempts, time to insert the device, indwelling time, complications, requirements for additional vascular access devices, and patient satisfaction. The incidence of catheter failure was significantly lower in the MCs group (10.71%) than in the LPCs group (20.54%; odds ratio [OR] 0.46; 95% confidence interval [CI], 0.22–0.99; P = 0.043). Additionally, MCs had longer median indwelling times (7 d vs. 5 d; P < 0.001), fewer complications (13.39% vs. 27.68%; OR 0.40; 95% CI, 0.20–0.80; P = 0.008), and required fewer additional devices (4.46% vs. 16.07%; OR 0.24; 95% CI, 0.09–0.68; P = 0.004). These findings suggest that MCs are a superior choice for vascular access devices in patients undergoing bariatric surgery. Trial registration: Trial registered at ClinicalTrials.gov (NCT06031545 11/09/2023).